Aplicación de las relaciones de transferencia a las Alianzas Estratégicas (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2012)
This paper proposes the application of some of the OCDE transfer pricing methods, defined to value the intragroup interchanges with fiscal purpose, to the management of strategic alliances. The main goal is to offer an objective basis to structure the relation between the partners in an alliance. This is an aspect of extreme importance so as to diminish the real and perceived risks of opportunism in this type of company relations characterized by their great unsteadiness. The formulations takeshape for a selection of alliances: horizontal, vertical, for the use of an installation incommon and for the development of innovation.
Keywords: Transfer Pricing; Strategic Alliances.